Studies on Synthesis, Spectral Properties and Antimicrobial Activity of Biologically Potent Manganese(II) Complexes - Sharma, Kripa; Mishra, Rakhi; Singh, R.V. (Asian Journal of Chemistry, 2010)
The synthesis, spectroscopic characterization and antimicrobial activities of some unsymmetrical manganese(II) complexes of thioazomethines including benzothiazolines having NS donor set have been described. The 1:1:1 reactions of hydrated manganese chloride with monobasic bidentate azomethines resulted in the formation of coloured solids which have been characterized by elemental analysis, molecular weight determination, conductance and magnetic measurements. The infrared, electronic and electron spin resonance spectral studies indicated tetrahedral geometry for the resulting complexes. These thio ligands along with their complexes have been screened in vitro against a number of pathogenic fungi and bacteri to assess their growth inhibiting potential.